Three-dimensional reinforcement design method and program realization for prestressed concrete box-girder bridges based on a specific spatial lattice grid model. (15th November 2018) - Sun, Yuan; Xu, Dong; Chen, Bin; Xu, Fang-Yuan; Zhu, Hong-Ping
Highlights: Specific beam-oriented model for complete integral effects of concrete box-girder bridge. Three layers of stresses of plates to finely differentiate the structural behaviours. Stress based reinforcement method for in-plane shear resistance of the top and bottom plates. Automatic 3D reinforcement calculation flow based on limit state design method. Abstract: Reinforcement with prestressed steel tendons to prevent cracking is a major design procedure for most concrete box-girder bridges. They provide acceptable performance even though they do not cover all of the principal stress directions of the structural members because ordinary steel bars also play an important role in resisting external loads. However, with the limitations of current design methods, a plane model is always used as a standard for designers for manual performance of the procedure, but it does not provide sufficient information for the reinforcement of easily overlooked parts from the view of integral three-dimensional effects. Design experiences and detailing requirements must therefore be used extensively, leading to either a waste of materials or a greater likelihood of unexpected damage to members. To address this issue, this study proposes a solution for the reinforcement of prestressed concrete box-girder bridges with a new reinforcement method combined with a specific spatial lattice grid model. The model, which finely differentiates the stress sources of the members and especially emphasizes the in-plane stresses of the top and bottom plates, facilitates the establishment of a stress-based reinforcement method to completely consider the three-dimensional effects of prestressed concrete box-girders and provide the necessary information associated with current bridge codes. The method was implemented as the module of a bridge software with an automatic design function. The effectiveness of the method is demonstrated and discussed via numerical examples.